Exercise Instructors for Older Adult Fitness: A Review of the Literature. Issue 3 (8th September 2020) - Harvey, Kelsey; Griffin, Meridith
ABSTRACT: Group-exercise instructors are a vital social determinant of exercise enjoyment, attendance, and adherence. Instructors also affect the degree to which physical cultures are socially inclusive. In order to elucidate the roles that instructors play in affecting these outcomes, we conducted a scoping review. Scoping reviews are a preliminary method for assessing the breadth and depth of existing literature in order to identify key themes and gaps therein. Based on Arksey and O'Malley's (2005 ) framework, we identified 52 articles and book chapters, 33 of which were older-adult specific, using a university search engine that simultaneously searches multiple databases. We conceptually mapped the literature, which revealed instructors' vital roles as: (1) constructors of group social cohesion, (2) cultural intermediaries, (3) competent practitioners, (4) leaders and communicators, and (5) educators. Of these, the instructor's educative role lacks empirical attention. We conclude with implications for future research, practice, and policy.